Using augmented reality for learning naval operations - Correia, Anacleto (2021)
Augmented reality (AR) is a technology that extends the perception of human reality by allowing, for example, inserting virtual objects in real environments. With augmented reality, learning can be more effective with graphics and interactivity in the manipulation of content. With this work, we intend to apply the AR technology in a process of developing a solution in learning context. For this purpose, different types of devices were analyzed in order to select the type of equipment with better characteristics for use in teaching/learning solutions. An agile development process was tailored to be used in the development of AR applications. The process was then instantiated in the development of an AR solution for learning purposes of ships' maneuvers in formations in the context of naval operations. The effectiveness of the AR solution was then validated through statistical tests of data collected from a survey to a sample of users.